Comparative embryology of angiosperms - Johri, B. M. (Springer-Verlag, 1992)
COMPARATIVE EMBRYOLOGY OF ANGIOSPERMS is a review of the developmental processes leading to sexual reproduction in flowering plants. On the basis of embryological data and certain evidences from other areas of study, it lays special emphasis on the relationship among and within the families and orders of angiosperms. Occasionally, inaccuracies in observation and interpretation are pointed out, alternative interpretations offered, gaps in our knowledge highlighted, and prospects outlined. The text is documented with 36 tables, 376 figures, and about 5000 literature citations, which contribute to making this book comprehensive. Besides students and research workers interested in angiosperm embyology, taxonomists, plant breeders, agriculturists, and horticulturists will also find much useful information in this treatise.